Imam Mahdi in Sunni Tradition: Differences in Beliefs and Interpretations - Nur, Faisal M. (Abrahamic Religions: Jurnal Studi Agama-Agama, 2023)
The concept of Imam Mahdi holds a special place, but differences in beliefs and interpretations regarding Imam Mahdi within the Sunni community have led to confusion and even disputes among Muslims. To gain a deeper understanding of how Imam Mahdi is viewed from the perspective of Sunni tradition and the differences in beliefs and interpretations, this research will delve into the complexities of these views and identify different frameworks of understanding. This will help us appreciate the diversity of Islamic thought and how these understandings impact religious practices and the perspectives of Muslim communities. Furthermore, it will underscore the importance of inter-sectarian dialogue in today's increasingly complex Muslim society. The research method employed in this study is a literature review, based on the analysis and synthesis of relevant literature on the specific research topic. Titled "Imam Mahdi in the Perspective of Sunni Tradition: Differences in Beliefs and Interpretations," the findings suggest that al-Mahdi plays a crucial role in elevating the status of Islam and the Muslim community to their true potential. This will enable the Muslim community to shield itself from the negative effects of materialistic modernization and blind imitation of traditions that may not align with Islamic values, as conveyed by the Prophet Muhammad (peace be upon him). The term 'Mahdi' refers to an eschatological figure in Islam, believed to come in the end times to establish justice throughout the world. In the Shia Islamic perspective, Mahdi is the twelfth Imam, and according to their beliefs, he will appear at some point in the future.